The IMF's Government Finance Statistics Yearbook : Maps of Government for 74 Countries. (IMF Working Papers; Working Paper ;, 2011)
A useful but little known feature of the IMF's Government Finance Statistics Yearbook (GFSY) is the information on the structure of governments. Institutional tables, included in the GFSY, provide detail on the central, state, and local levels of governments, social security, and extrabudgetary units. We refer to the main levels of government as GL1, GL2, and GL3 in ascending order of institutional coverage. We present maps of the various levels of government for 74 countries to illustrate the usefulness of this database and make it more accessible to users. The maps provide information about how centralized or decentralized government finances and employment are and their size relative to the overall economy. Government map data facilitate the monitoring of fiscal policy and fiscal rules.